2020
DOI: 10.1124/dmd.119.090043
|View full text |Cite|
|
Sign up to set email alerts
|

Coordinated Regulation of UGT2B15 Expression by Long Noncoding RNA LINC00574 and hsa-miR-129-5p in HepaRG Cells

Abstract: Recent studies have shown that microRNAs and long noncoding RNAs (lncRNAs) regulate the expression of drug metabolizing enzymes (DMEs) in human hepatic cells and that a set of DMEs, including UDP glucuronosyltransferase (UGT) 2B15, is downregulated dramatically in liver cells by toxic acetaminophen (APAP) concentrations. In this study we analyzed mRNA, microRNA, and lncRNA expression profiles in APAP-treated HepaRG cells to explore noncoding RNA-dependent regulation of DME expression. The expression of UGT2B15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Recent studies have suggested that lncRNAs are highly relevant to drug metabolism through the regulation of drug metabolizing enzyme genes [76][77][78]. In addition to HNF1α-AS1 and HNF4α-AS1, several other lncRNAs have also been identified in the regulation of expression of drug metabolizing enzyme genes, such as LINC00574 in the regulation of UGT2B15 expression, and contribution to susceptibility of drug-induced liver injury (DILI), for example LINC00844 [79,80]. These works have opened a novel area in the field of drug metabolism and DILI, which requires further studies to provide answers for some fundamental questions.…”
Section: Roles Of Hnf1α-as1 and Hnf4α-as1 In Physiologic Functions Including Drug Metabolismmentioning
confidence: 99%
“…Recent studies have suggested that lncRNAs are highly relevant to drug metabolism through the regulation of drug metabolizing enzyme genes [76][77][78]. In addition to HNF1α-AS1 and HNF4α-AS1, several other lncRNAs have also been identified in the regulation of expression of drug metabolizing enzyme genes, such as LINC00574 in the regulation of UGT2B15 expression, and contribution to susceptibility of drug-induced liver injury (DILI), for example LINC00844 [79,80]. These works have opened a novel area in the field of drug metabolism and DILI, which requires further studies to provide answers for some fundamental questions.…”
Section: Roles Of Hnf1α-as1 and Hnf4α-as1 In Physiologic Functions Including Drug Metabolismmentioning
confidence: 99%
“…The findings suggest a possible involvement in the regulation of mitochondrial function and ROS(Reactive Oxygen Species, ROS) levels and thus in the development of PD [ 57 ]. hsa-miR-129-5p has also been found to be differentially expressed in both AD and PD and is possibly involved in the development of Huntington’s disease, suggesting that this gene may be involved in a common pathogenic mechanism of neurodegenerative diseases, although the exact mechanism is not yet clear [ 58 ]. We also expect that future related studies can refer to the ceRNA network we constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, LINC00844 was significantly down-regulated in a concentration-dependent manner in response to APAP exposure, and it showed the positive relation with the mRNA levels of CYP3A4, 2E1, SULT2A1, PXR, and HNF4A (Li et al, 2020). Another lncRNA LINC00574 has been proved to coordinately regulate expression of a phase II drug-metabolizing enzyme UGT2B15 by interacting with miRNA miR-129 in HepaRG cells treated with APAP (Yu et al, 2020).…”
Section: Roles Of Histone Modifications In Induction Of Cyp Expressio...mentioning
confidence: 94%